Optimal control analysis and Practical NMPC applied to refrigeration systems. (December 2020) - Bejarano, G.; Ortega, M.G.; Normey-Rico, J.E.; Rubio, F.R.
Abstract: This work is focused on optimal control of mechanical compression refrigeration systems. A reduced-order state-space model based on the moving boundary approach is proposed for the canonical cycle, which eases the controller design. The optimal cycle (that satisfying the cooling demand while maximizing efficiency) is defined by three variables, but only two inputs are available, therefore the controllability of the proposed model is studied. It is shown through optimization simulations how optimal cycles for a range of the cooling demand turn out not to be achieved by keeping the degree of superheating to a minimum. The Practical NMPC and a well-known feedback-plus-feedforward strategy from the literature are compared in simulation, both showing trouble in reaching the optimal cycle, which agrees with the controllability study. Highlights: Optimal control of mechanical-compression refrigeration systems is tackled. A reduced-order dynamic model with only three states is proposed. A COP-based global optimization and a controllability study are addressed. The Practical Nonlinear Model Predictive Control (PNMPC) is applied. Comparison between the PNMPC and a feedback-plus-feedforward strategy in simulation.